On-farm conservation of rice biodiversity in Nepal: A simultaneous estimation approach - Van Dusen, M. Eric; Gauchan, Devendra; Smale, Melinda (Wiley, 2007)
This paper presents an empirical case study about farmer management of rice genetic resources in two communities of Nepal, drawing on interdisciplinary, participatory research that involved farmers, rice geneticists and social scientists. The decision‐making process of farm households is modelled and estimated in order to provide information for the design of community‐based conservation programmes. A bivariate model with sample selection examines the simultaneous process of whether farmers decide to plant landraces or modern varieties, and whether the landraces they choose to plant constitute the genetic diversity of interest for future crop improvement. Findings show that the two landrace choices are affected by different social and economic factors, but in certain cases the decision processes are interrelated. Policies to promote the conservation of local rice diversity will need to take both processes into account.